The end of loneliness [large type] - Wells, Benedict, 1984- (Thorndike Press large print core, 2019)
"A kaleidoscopic and heartfelt family saga, as well as a deeply felt meditation on the power of memory, The End of Loneliness explores the invisible forces and currents that can change our lives in an instant, and asks us all to consider, If you spend all your life running in the wrong direction, could it be the right one after all?"--